1988
DOI: 10.1002/clc.4960111004
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity during five years after myocardial infarction and its relation to infarct size

Abstract: Summary:In 809 patients with a recent myocardial infarction, morbidity during 5-year follow-up was assessed. The overall 5-year mortality rate was 33% (39% in patients with larger infarcts and 26% in patients with smaller infarcts) as judged from maximum serum enzyme activity (p < ,001). In terms of morbidity, no significant association with estimated infarct size was observed. Patients with smaller infarcts tended to have a higher reinfarction rate and were rehospitalized more often, whereas a similar proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…Elderly humans who are sedentary appear to lose the preconditioning benefits of preinfarction angina, although the protection was seen in counterparts who exercised (1,116). Given the relationship between infarct size and mortality (50,88), exercise is postulated to promote survival by delaying cell death during metabolic challenge, reducing the mass of infarcted tissue.…”
Section: What Is the Relationship Between Exercise And Infarct Size?mentioning
confidence: 99%
“…Elderly humans who are sedentary appear to lose the preconditioning benefits of preinfarction angina, although the protection was seen in counterparts who exercised (1,116). Given the relationship between infarct size and mortality (50,88), exercise is postulated to promote survival by delaying cell death during metabolic challenge, reducing the mass of infarcted tissue.…”
Section: What Is the Relationship Between Exercise And Infarct Size?mentioning
confidence: 99%
“…Two major manifestations of reperfusion injury are myocyte death (infarction) and microvascular damage (no-reflow). Given that long-term prognosis has been linked to both size of infarction [1][2][3] and the extent of reflow, 4,5 strategies aimed to decrease infarct size or limit the amount of no-reflow have significant potential as adjuvant therapies.…”
mentioning
confidence: 99%
“…Other than chronic moderate ethanol consumption (Kehl et al 2003), exercise training is the only stimulus demonstrated to sustain myocardial protection against infarction over such an extended period of time. This finding continues to be extremely relevant from a clinical standpoint, as myocardial infarction affects over 1 million Americans annually (National Health and Nutrition Examination Survey III, 2000), and size of infarction correlates inversely with chance of both short‐term (Miller et al 1995) and long‐term survival (Herlitz et al 1988).…”
mentioning
confidence: 99%